In‘ikāsāt al-Manhaj al-Mustaqillī fī Ta‘allum al-Lughah al-‘Arabiyyah: Murāja‘ah Manhajiyyah li-l-Adabiyyāt: انعكاسات المنهج المستقل في تعلم اللغة العربية: مراجعة منهجية للأدبيات - Rawi Nasution, Muhammad Fadlan; Nasution, Sahkholid (Institut Muslim Cendekia, 2025)
The suitability of the curriculum in Arabic language learning is currently very much needed to achieve learning goals, however, Arabic language learning based on the current independent curriculum still has difficulties and is not in accordance with the goals of the curriculum that should be. This study aims to analyze the implications of the Merdeka Curriculum in Arabic language learning using a Systematic Literature Review (SLR) approach. The Merdeka Curriculum, implemented in Indonesia since 2022, seeks to enhance teachers’ autonomy and students’ active participation in learning. However, its implementation in Arabic language education presents both opportunities and challenges. This study systematically reviews literature from 2021–2025, sourced from Google Scholar and Semantic Scholar, to identify trends, benefits, and challenges associated with the curriculum’s application. The findings indicate that the Merdeka Curriculum fosters student-centered learning, increases motivation, and promotes a contextual learning approach. Nevertheless, challenges include teachers’ adaptation difficulties, lack of sufficient training, and students’ struggles in mastering Arabic under the new system. This study provides valuable insights for educators and policymakers in refining the implementation of the Merdeka Curriculum for Arabic language learning.